Mengadaptasikan gaya pembelajaran pelajar ESL: satu kajian kes pelajar tahun satu di UKM - Rosniah Mustaffa (Penerbitan UKM, 2007)
Most instructions at the tertiary level in Malaysia are given in an auditory and visual manner in which students have to listen to lectures, class discussions and presentations.The main focus of this case study was to discover whether less proficient students of Bachelor of Arts in English Language Studies (B.A ELS) at Universiti Kebangsaan Malaysia can “stretch” their learning styles outside their preferred modes namely the auditory and visual styles, and working individually over two semesters (eight months) of practice. The tools in collecting the data were Reid’s (1984, cited in Reid, 1995)perceptual learning style preference questionnaire, journal writing, semi-structured interviews and observations. The findings from this study were: 1) the majority of the students in this study had at least kinaesthetic and/or tactile as their major perceptual learning style and the majority of them had also chosen working in a group as their major learning style; 2) all the students had the same common reactions in terms of having difficulties in completing visual or auditory tasks, normal way of studying, and the abilities to make the new ways of visual and auditory techniques of learning work when introduced and practised in class. They also had the same negative reactions to incongruent styles